A DENSITY FUNCTIONAL THEORY STUDY ON STRUCTURE AND PROPERTIES OF BENZENE AND BORAZINE-BASED CHROMOPHORES - GHIASI,REZA (Sociedad Chilena de Química, 2014)
Density functional theory (DFT) calculations were employed to investigate the structural characteristics, electronic properties, and nonlinear optical properties of borazine-based chromophores at B3LYP/ 6-311G(d,p) level. We studied the effects of various donor and acceptor substituents (H, F, Cl, Br, Me, NH2, OH, COOH, CHO, CN, NO2) on the stability, dipole moment, polarizability, frontier orbitals, structure, the most intense electronic transition, and hyperpolarizabilities. These calculations indicate B-isomer is more stable than N-isomer. On the other hand, the most stable isomer confirms the minimum polarizability and maximum hardness principles in the most molecules. Also, we obtained good linear relations between some of the studied properties. The predicted first hyperpolarizability also shows that the substituted molecules might have a reasonably good nonlinear optical (NLO) behavior.